A New-Age for Biologic Therapies: Long-Term Drug-Free Therapy with BiP? - Shields, Adrian M.; Panayi, Gabriel; Corrigall, Valerie (Frontiers in Immunology, 2012)
Heat shock proteins (HSPs) and other members of the much broader stress protein family have been shown to play important roles in coordinating multiple phases of immunological reactions; from facilitating immunological recognition, to promoting and regulating immunological responses and finally augmenting the resolution of inflammation and return to immunological homeostasis. In this review, we consider the challenges facing the stress protein field as we enter 2012; in particular we consider the role that HSPs and stress proteins may play in the initiation and termination of immunological responses. Special attention is afforded to the resolution-associated molecular pattern, binding immunoglobulin protein (BiP, also known as glucose regulated protein-78). We review the evidence that resolution-promoting proteins such as BiP may herald a new generation of biologics for inflammatory disease and reflect on the challenges of achieving clinical remission in rheumatoid arthritis with novel therapeutics and correlating clinical remission with immunological parameters of resolution of inflammation.